2009
DOI: 10.1111/j.1600-0404.1980.tb02991.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic atrophy in experimental vitamin B12 deficiency in monkeys

Abstract: The clinical findings and pathological changes of the visual pathway of vitamin B12 deficient monkeys have been described. The cellular morphology and counts of the peripheral blood and bone marrow remained normal during the study (nine deficient, three controls: one still alive in each group). Visual impairment was noted in all seven of the deficient animals that were evaluated by clinical observations. Ophthalmoscopic examination disclosed optic atrophy in six of the seven deficient monkeys. Degeneration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Neuropathological studies showed symmetrical degeneration of the peripheral visual pathway and spinal cord white matter, diffuse degeneration of cerebral white matter, and degeneration of cranial nerve roots. Lesions were indistinguishable from those found in humans with vitamin B 12 deficiency (Agamanolis et al, 1976; Chester et al, 1980). …”
Section: 0 Vitamin Deficiency Chemicals and Neurological Diseasementioning
confidence: 65%
See 1 more Smart Citation
“…Neuropathological studies showed symmetrical degeneration of the peripheral visual pathway and spinal cord white matter, diffuse degeneration of cerebral white matter, and degeneration of cranial nerve roots. Lesions were indistinguishable from those found in humans with vitamin B 12 deficiency (Agamanolis et al, 1976; Chester et al, 1980). …”
Section: 0 Vitamin Deficiency Chemicals and Neurological Diseasementioning
confidence: 65%
“…Optic nerves in cobalamin deficiency reportedly showed demyelination in the central portion of the retrobulbar optic nerve after rats were subjected to daily inhalation of cyanide gas for 52 weeks (Oku et al, 1991). Optic neuropathy with visual impairment occurs in cobalamin-deficient monkeys (Chester et al, 1980). …”
Section: 0 Vitamin Deficiency Chemicals and Neurological Diseasementioning
confidence: 99%
“…In more detail, in the present article, we reported two cases of nutritional optic neuritis in rhesus monkeys that were clearly attributable to a prolonged insufficient dietary intake of folic acid, in the absence of other relevant nutritional deficiencies, including of cobalamin, [11][12][13] and in the absence of other clinical signs of disease or dysfunction. Given that our monkeys lived and were handled in a highly controlled environment, a number of potential etiological factors, such as exposure to toxic substances or the habitual consumption of substances of abuse, could be safely excluded as contributing causes.…”
Section: Discussionmentioning
confidence: 68%
“…7 Several studies suggested a crucial role of B-complex vitamin deficiencies in nutritional optic neuropathy 10 ; in particular, cobalamin (B 12 ) deficiency, commonly related to inborn errors of metabolism, such as in pernicious anemia, has been proven to cause optic neuropathy both in humans and animals. [11][12][13] Folic acid (B 9 ) deficiency also has been proposed as a possible etiological factor for optic neuritis. 5,6 As a confirmation, specific therapy with prolonged daily supplementation of folic acid was demonstrated to produce clinical improvement, eventually leading to a complete recovery from optic neuritis after a long time.…”
mentioning
confidence: 99%
“…OCT can be used to obtain cross-sectional images of the peripapillary RNFL, as this has been shown to be decreased especially in the temporal quadrant with involvement of the papillomacular bundle. 79 , 81 , 82 This reduction has been attributed to a decrease in myelinisation, since vitamin B12 is a major co-factor in the synthesis of myelin. Interestingly, thinning of the RNFL can be seen before patients have manifest VF defects.…”
Section: Review Of Diseasesmentioning
confidence: 99%